Predictors for developmental delay in children with cerebral palsy and at-risk children - Rashikj Canevska, Olivera; Karovska Ristovska, Aleksandra; Bojadzhi, Marija (Index Copernicus, 2019)
The first three years of life (zero to three) are a period of great importance when discovering the congenital, as well as the acquired disorders and developmental delays. Recognizing milestones and manifestations of certain behaviors helps us identify developmental delays and disruptions. With this research we intended to determine the segments of developmental achievements and developmental discrepancies of psycho-motor development (general development achievements, motor functions, surrounding motor functions and communication) in infancy and early childhood (zero to three years old) in three groups of respondents. The research sample included 104 respondents. Sixty-three of them had been diagnosed with cerebral palsy (thirty-three were without comorbidity convulsions, and thirty were with comorbidity convulsions-epilepsy), and forty-one respondents were born with a risk factor for a developmental delay. The research was conducted using the standardized developmental instrument Chuturic Developmental Scale for evaluation of the psycho-motor development, which encompasses oculomotorics, emotional development, speech, hearing-motor reactions, communication, socialization and verbalization, of infants and small children. The analysis of results concluded that there is a discrepancy in the developmental achievements of the three groups of respondents. Based on analysis of the values of the Global Development Coefficient (GDC), we have determined that the most affected group is the group of children with cerebral palsy and comorbidity convulsions where the average value of GDC is 47.77. Early and precision diagnostics, as well as knowledge of the developmental characteristics of different categories of developmental delays will improve the prognosis and contribute to better utilization of the brain plasticity in children with cerebral damage and children born at risk. Early intervention and stimulation are more than necessary to maximize the child's full potential, reduce the primary effects of the damage or prevent secondary damages and difficulties.